Selection of wild hosts for feeding by passion vine hopper Scolypopa australis (Walker) (Hemiptera Ricaniidae) in the Bay of Plenty - Logan, D.P.; Allison, P.A.; Stannard, K. (New Zealand Plant Protection, 2002)
Passion vine hopper Scolypopa australis (Walker) (Hemiptera Ricaniidae) a pest of kiwifruit occurs on a wide range of native and introduced plants that are probably not equally preferred as hosts First instar nymphs and adults were observed on 69 and 53 respectively of 42 plant species found at varying frequency in a survey of gullies adjacent to kiwifruit orchards in the Bay of Plenty In choice tests with four plant species common in gullies firstinstar nymphs and adults preferred the native species mahoe (Melicytus ramiflorus) Under nochoice conditions survival from first to late instar was also best on mahoe Of 10 plant species in a nochoice test adults survived best and laid most eggs on the native species wineberry (Aristotelia serrata)